LINGUISTIC FEATURES OF PHRASEOLOGICAL UNITS RELATED TO THE FIELD OF ECONOMICS IN THE ENGLISH AND UZBEK LANGUAGES - Muxiddinova Hilola (TADQIQOTLAR, 2025)
Abstract: Phraseological units represent an important layer of language that reflects both linguistic structure and cultural worldview, playing a significant role in the expression of abstract concepts in specialized fields such as economics. This article explores the linguistic features of phraseological units related to the field of economics in the English and Uzbek languages, with the aim of identifying their structural, semantic, and functional characteristics. Economic phraseology is of particular interest due to its metaphorical nature and its widespread use in professional discourse, media texts, and everyday communication. The study applies descriptive and contrastive methods to analyze economic phraseological units selected from dictionaries, economic texts, and media sources. Special attention is paid to their semantic motivation, metaphorical foundations, and degree of idiomaticity. The analysis reveals that many economic phraseological units in both languages are based on universal conceptual metaphors such as economy as movement, struggle, growth, and mechanism, while others reflect culture-specific images and national experience.